Foundations of athletic training prevention, assessment, and management - Anderson, Marcia K.; Barnum, Mary (Philadelphia Wolters Kluwer Health, 2017)
"Comprehensive, and evidence-based, Foundations of Athletic Training, 6th Edition integrates basic medical concepts and related scientific information to help athletic trainers and students develop a strong foundation in athletic training best practices. Using a problem-solving approach to the prevention, recognition, assessment, management, and disposition of sports-related injuries and diseases, the text helps students learn to think like practitioners and is fully aligned with the BOC competencies. This 6th Edition has been updated throughout to reflect current best practices in the field and includes four new chapters, new and updated references, and a powerful suite of online learning resources that save instructors time and help students succeed."--Publisher's description
Foundations for the prevention of sports injuries. Ch. 1. Injury care and the athletic trainer -- Ch. 2. Preparticipation examination -- Ch. 3. Protective equipment -- Protective taping and wrapping -- Clinical examination of diagnosis. Ch. 5. Evidence-based health care -- Ch. 6. Clinical assessment and diagnosis -- Ch. 7. Acute injuries : assessment and disposition -- Ch. 8. Assessment of body alignment posture and gait -- Ch. 9. Psychosocial intervention and patient care -- Therapeutic interventions. Ch. 10. Tissue healing and wound care -- Therapeutic medications -- Ch. 12. Therapeutic modalities -- Ch. 13. Therapeutic exercise program -- Conditions of the lower extremity. Ch. 14. Lower leg, ankle, and foot conditions -- Ch. 15. Knee conditions -- Ch. 16. Pelvic, hip, and thigh conditions -- Conditions of the upper extremity. Ch. 17. Shoulder conditions -- Ch. 18. Upper arm, elbow, and forearm conditions -- Ch. 19. Wrist and hand conditions -- Conditions to the axial region. Ch. 20. Head and facial conditions -- Ch. 21. Cervical and thoracic spinal conditions -- Ch. 22. Lumbar spinal conditions -- Ch. 23. Throat, thorax, and visceral conditions -- Systemic conditions and special considerations. Ch. 24. Cardiovascular disorders -- Ch. 25. Neurological conditions -- Ch. 26. Respiratory tract conditions -- Ch. 27. Gastrointestinal conditions -- Ch. 28. Endocrine conditions -- Ch. 29. Environmental conditions -- Ch. 30. Athletes with physical disabilities -- Ch. 31. Common infectious diseases -- Ch. 32. Dermatology
Includes bibliographical references and index.
Keywords: Sports injuries; Sports injuries -- Prevention; Sports injuries -- Diagnosis; Sports physical therapy